PENGARUH FINANCIAL DISTRESS, KARAKTERISTIK EKSEKUTIF, DAN FAMILY OWNERSHIP TERHADAP TAX AVOIDANCE - Riza Dwi Astriyani; Mohamad Safii (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This study aims to determine the effect of financial distress, executive characteristics and family ownership on tax avoidance. The data used are property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2016 – 2020. This study is a quantitative study using secondary data. In taking the sample using purposive sampling technique, and the number of samples obtained and used in this study amounted to 40, namely from 8 companies with 5 years of research. The data processing in this study used the Eviews version 9. The results showed that financial distress, executive characteristics and family ownership had a simultaneous (simultaneous) effect on tax avoidance. In addition, this study proves that financial distress and executive characteristics have no significant effect on tax avoidance, while family ownership has a positive and significant effect on tax avoidance. And 46.96% of tax avoidance can be explained by financial distress variables, executive characteristics and family ownership. While the remaining 53.04% can be explained by other variables not examined.